Upaya Meningkatkan Partisipasi Politik Perempuan Dalam Keterwakilan di Legislatif - Muhammad Ar Rafii; Elan Jaelani (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
his research aims to discuss the problems in fulfilling the quota for women's political participation in the legislature and the efforts of state institutions to increase women's participation in general elections. This research uses a qualitative method with a normative juridical approach. That is an approach based on the main legal material by examining theories, concepts, legal principles, and laws and regulations related to this research. The results of the study show an increase in women's representation in the legislature, but the representation rate is still far away because the last legislative election practice system in 2019 used an open proportional system, and there is still a low level of public understanding of women's representation in the legislature which is a form of gender equality. The efforts made by the relevant institutions, namely the KPU and Bawaslu, in improving these problems are to ensure the fulfillment of the 30% quota of women's representation in the nomination of legislative members and to provide strict sanctions for those who do not fulfill it. This effort reflects the need for strict supervision to ensure the implementation of rules in achieving the goal of women's representation. Thus, improving the electoral system, increasing public knowledge, and applying strict sanctions are necessary to achieve the affirmative targer of women in politics in Indonesia.